2012
DOI: 10.3329/bjch.v35i1.10367
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Childhood Idiopathic Nephrotic Syndrome with Asthma, Hypertension, Complement C<sub>3</sub>, Urinalysis

Abstract: A prospective observational study of 43 children with idiopathic nephrotic syndrome (INS) were selected randomly out of 480 children admitted with the disease at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2003 to January 2005. Aim of this study was to correlate the difference in frequency of atopic attack, hypertension, complement c3 level and urinalysis in different types of Idiopathic nephrotic syndrome. Result: Among 43 children with idiopathic nephrotic syndrome (INS), 24 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…In new, in our study, there was a higher increase in systolic blood pressure in the SSNS group compared to the significant SRNS group, but there was no difference in diastolic blood pressure in the SRNS and SSNS groups. This compares with a 2011 study in Bangladesh in which there were more hypertension events found in the SRNS group than SSNS (p > 0.05) [2] and in line with research in Indonesia 2016 where blood pressure found in the SSNS group was higher than the SRNS group but not statistically meaningful [3]. Another study by Mamesah 2019 found the average systolic and diastolic blood pressure of the SRNS group compared to the SSNS group [9].…”
Section: Figure 1: Systolic Blood Pressure Boxplot Chart In Steroid-resistant Nephrotic Syndrome (Ns) and Steroid Sensitive Ns Groupssupporting
confidence: 83%
See 3 more Smart Citations
“…In new, in our study, there was a higher increase in systolic blood pressure in the SSNS group compared to the significant SRNS group, but there was no difference in diastolic blood pressure in the SRNS and SSNS groups. This compares with a 2011 study in Bangladesh in which there were more hypertension events found in the SRNS group than SSNS (p > 0.05) [2] and in line with research in Indonesia 2016 where blood pressure found in the SSNS group was higher than the SRNS group but not statistically meaningful [3]. Another study by Mamesah 2019 found the average systolic and diastolic blood pressure of the SRNS group compared to the SSNS group [9].…”
Section: Figure 1: Systolic Blood Pressure Boxplot Chart In Steroid-resistant Nephrotic Syndrome (Ns) and Steroid Sensitive Ns Groupssupporting
confidence: 83%
“…Hypertension that occurs in nephrotic syndrome (NS) is an event that will cause a poor prognosis in cases of NS both in the Steroid Resistant NS (SRNS) group and in the steroid sensitive NS (SSNS) group [1]. According to a 2011 study in Bangladesh found, more hypertension incidence was found in SRNS compared to the SSNS group [2]. However, in another study in Manado, the average systolic and diastolic blood pressure was higher in the SSNS group than in the SRNS group [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meskipun kekambuhan adalah sifat umum SN, 90-95% anak dengan SNKM responsif terhadap terapi steroid dengan menyelesaikan klinis remisi biokimia dan memiliki prognosis jangka panjang yang sangat baik. 7 Sindrom nefrotik pada anak yang didiagnosis secara histopatologik sebagai lesi minimal, sebagian besar akan memberikan respons terhadap pengobatan steroid. Pada SN lesi nonminimal sebagian besar tidak memberikan respons terhadap pengobatan steroid.…”
unclassified